Mikroświat inności dorosłych osób z niepełnosprawnością intelektualną – raport z badań - Gutowska, Anna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The text is an attempt to present the phenomenon of experiencing otherness by adult people with mental disability. The author presents survey results which are a part of a bigger project researching the microworlds of adults with intellectual disability. In the research, both as the strategy of collecting the research materials and the method of their analysis, the methodology of constructing grounded theory by Kathy Charmaz was used. 14 adults with intellectual disability, attendees of the Community Centre of Self-Help, were researched, as well as 14 attendants (including parents and the centre’s employees). The results showed otherness as a specific phenomenon experienced by all the surveyed people with intellectual disability.